Rethinking America Hedrick Smith. - Smith, Hedrick (New York Random House, 1995)
Measuring this country against its major competitors, Smith shows how global competition has radically altered the way people work, what schools need to teach, and the nature of power and people's relationships on the job. With one insightful story after another, he reveals what goes on inside grade school and high school classrooms and inside big corporations and small companies in the three main capitalist economies; how that affects our future; and why today's greatest need is a new mind-set.
In revealing portraits, Smith contrasts how American CEOs think at giants such as GM, Boeing, Motorola, compared to CEOs at Germany's Daimler-Benz and Deutsche Bank or at Japan's Toyota or Mitsubishi. He discloses how differently decisions are made and power is wielded in the corporate boardrooms of America, Germany, and Japan. He shows us what workers think and do in these rival economies and how the lives of workers at companies such as Ford and Motorola were transformed once management began rethinking its approach. Education is where the race begins. Smith contrasts what American grade school teachers emphasize, compared with the skills and values taught elsewhere. He shows how businessmen in Germany and Japan cooperate with educators in creating programs to prepare "mid-kids" - average high school students - for solid careers and how innovative American communities are developing similar strategies.
pt. 1. American challenged : mired in the mind-set of success: New mind-set/old mind-set--challengers versus champions : Sharp versus RCA--how singles beat home runs ;The new global game--people, quality, flexibility, trust : what GM and Mercedes had to learn from Toyota ; The success reflex : IBM--seing change as a threat, not as an opportunity -- pt. 2. Education : rethinking schools for the new global game: School--where the race begins : teamwork or tracking--which works best? ; High school--the neglacted majority : whose mid-kids are on track for the global economy? ; Harlem--teaching habits of mind : it's not "academic," it's "real life" ; Wisconsin--business and schools as partners : youth apprenticeships--a New Deal for the neglected majority -- pt. 3. Business : matching mind-sets with the competition: People : protecting and developing human capital ; Partnership : the turnaround at Ford--"We-we" instead of "Us versus them" ; Power sharing : owners, managers, and workers--"sitting in one boat" ; Stakeholders versus shareholders : gaining the long-term edge in the boardroom ; The network : Mitsubishi's Mutual Protection Society--the corporate clan ; Counterattack : Motorola--no market sanctuary for the Japanese -- pt. 4. Public/private : government and business as collaborators : Europe's grand coalition : Boeing and the challenge from Airbus ; America's industrial partnership : Sematech--Reagan's radical rescue plan -- Conclusion: The unfinished agenda : high performance and the perpetual revolution.
Includes bibliographical references (pages [421]-426) and index.
Keywords: Benchmarking (Management) -- United States; Technological innovations -- Economic aspects -- United States; Competition, International; United States -- Economic conditions -- 1981- .; United States -- Economic policy -- 1981-1993.; United States -- Economic policy -- 1993- .